Development of a Fall Risk Assessment Smartphone Application - Thirumalaya, Balaraman; Mohamodhossen, Maysoon Hanaa (INTI International University, 2018)
Background & Objective: Falls are major cause of injury among older adults. This study was aimed to develop a smartphone application that can be used to assess the fall risk among the elderly population.